Efectos de la aplicación de productos orgánicos y biológicos en el rendimiento del cultivo de Fréjol alegre (vigna sp.) en el cantón Cotacachi, provincia de Imbabura - Ayala Bravo, Alex Leonardo (2015)
The research "Effect of application of organic and biological products in crop yield Fréjol Alegre (Vigna sp.) In Cotacachi, Provincia de Imbabura," was held in the community of Green Heaven, belonging to the parish of García Moreno, Cotacachi, Provincia de Imbabura Province, in an altitudinal floor of 720 m and an average temperature of 23.5 ºC. Climate regime whose rainfall ranging from 800-1200 mm per year, with an average annual relative humidity is around 90%. The research work was carried out using a Design Randomized Complete Block (DBCA) with six treatments and three replicates, where the factors studied in the research were a variety of Fréjol and A. Factor organic and biological products. Tukey's test was used at 5% for the comparison of the averages of the variables when significant differences between treatments were determined. For testing the genotype from local seed bank of the Corporation organization Workshops Great Valley, with 98% of germination was used.